Transfer Pricing, Thin Capitalization, and Tax Haven Strategies: Do They Still Drive Tax Avoidance in the Post-AEOI Era? - Handi Sutanto; Agrianti Komalasari; Ninuk Dewi Kesumaningrum (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study examines the effect of transfer pricing, thin capitalization, firm size, and tax haven country utilization on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024 after the implementation of AEOI. The research uses a quantitative approach with a causal design and secondary data from financial reports. Multiple regression analysis is applied to test the relationship between variables. The results show that transfer pricing, firm size, and tax haven utilization have a significant effect on tax avoidance but in the opposite direction of the initial expectation, indicating lower tax avoidance. Meanwhile, thin capitalization shows a significant effect consistent with the hypothesis, where higher leverage increases tax avoidance. These findings suggest that tax behavior is influenced not only by company characteristics but also by regulatory pressure and transparency. Overall, the study provides evidence that stricter tax regulations have reduced aggressive tax practices.